Finite element model updating through derivative-free optimization algorithm - Li, Dan; Zhang, Jian (Mechanical systems and signal processing, 2023)
Finite element (FE) model of updating is the process of calibrating model parameters to improve the accuracy of numerical prediction. This goal is usually achieved by solving an optimization problem with the objective function measuring the misfit between simulated responses and experimental data. The sensitivity method is the predominate class of algorithms to FE model updating problems, and has opened a wide range of applications. However, this method often suffers from large errors due to linearization. To address this challenge, this paper proposes to utilize the unscented Kalman inversion (UKI) method to solve the FE model updating problems in a derivative-free manner. As an iterative optimization method, the UKI determines the new iterate using function values at a set of sample points rather than the derivative information. Implementation details, such as handling constraints during the optimization process, are presented in the paper. To validate the proposed UKI, model updating of a pedestrian bridge is conducted using the simulated and experimental data. Both validation examples show that the UKI is a competitive method for solving FE model updating problems. •The UKI method solves FE model updating problems in a derivative-free manner.•The UKI takes the effect of noises into account in a natural way.•Method is proposed to incorporate constraints during iterative process of the UKI.•The UKI is compared with the Levenberg–Marquardt algorithm.•The UKI is applied to updating a pedestrian bridge model using field test data.